Virulence assessment of six major pathogenic Candida species in the mouse model of invasive candidiasis caused by fungal translocation - Hirayama, Tatsuro (Sci Rep, 2020)
Gastrointestinal colonization has been considered as the primary source of candidaemia; however, few established mouse models are available that mimic this infection route. We therefore developed a reproducible mouse model of invasive candidiasis initiated by fungal translocation and compared the virulence of six major pathogenic Candida species. The mice were fed a low-protein diet and then inoculated intragastrically with Candida cells. Oral antibiotics and cyclophosphamide were then administered to facilitate colonization and subsequent dissemination of Candida cells. Mice infected with Candida albicans and Candida tropicalis exhibited higher mortality than mice infected with the other four species. Among the less virulent species, stool titres of Candida glabrata and Candida parapsilosis were higher than those of Candida krusei and Candida guilliermondii. The fungal burdens of C. parapsilosis and C. krusei in the livers and kidneys were significantly greater than those of C. guilliermondii. Histopathologically, C. albicans demonstrated the highest pathogenicity to invade into gut mucosa and liver tissues causing marked necrosis. Overall, this model allowed analysis of the virulence traits of Candida strains in individual mice including colonization in the gut, penetration into intestinal mucosa, invasion into blood vessels, and the subsequent dissemination leading to lethal infections.